Effects of alfalfa form and level on subacute acidosis - Healy, B.J.; Brandt, Robert T., Jr.; Gramlich, S.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eight ruminally cannulated crossbred steers (1225 lb) were used to investigate the effects of 5 vs 10% alfalfa hay or pellets on rumen characteristics during subacute acidosis. Alfalfa hay was obtained from one source, and alternate bales were either chopped (3- to 4-inch length) or ground and pelleted (3/8-inch pellet). Intake during the recovery period after feed challenges tended (P=.12) to be greater for diets containing 10% alfalfa. Duration of rumen pH below 5.5 was less for diets with chopped vs pelleted (P<.10) or 10 vs 5% (P<.05) alfalfa. Total volatile fatty acid (VFA) concentrations during the challenge ph ase and for the overall experimental period were increased (P<.05) when steers were fed 5 vs 10% alfalfa diets but were similar during the baseline and recovery periods. The higher pH and lower VFA concentration resulting from feeding 10% alfalfa diets suggest that steers fed a moderate amount of roughage can withstand greater fluctuations in intake without developing acidosis.
Keywords: Beef; Alfalfa; Subacute acidosis; Finishing cattle